EXTRACTION OF ESSENTIAL OIL FROM EUCALYPTUS LEAVES (EUCALYPTUS GLOBULUS) BY STEAM DISTILLATION AND ITS PHYSICOCHEMICAL AND MICROBIOLOGICAL CHARACTERIZATION - Puca Pacheco, Mercedes (2024)
The purpose of this research was to study the effect of mass and humidity of eucalyptus leaves on the oil extraction performance of Eucalyptus Globulus by steam distillation. A unifactorial design was used, using different masses of eucalyptus leaves fed to the extraction chamber while maintaining operating conditions. An oil with a density of 0,906 g/ml has been obtained, refractive index of 1,462 and absolute viscosity of 2,28 cp. A maximum yield of 1,28% m/m was obtained with a humidity of 60,95%. It was determined that as the humidity of the leaves for oil extraction decreases, a higher yield is obtained. The optimal conditions for extraction were the following: cooling water flow: 102,5 L/h; steam flow rate for extraction: 2,67 L/h; extraction chamber volume: 0,016 m3; which resulted in an oil volume of 56,32 mL for a mass of 4 kg of leaves. The volume of oil extracted depends directly on the mass of eucalyptus leaves and inversely proportional to the humidity of the leaves. Eucalyptus oil showed antimicrobial activity against Staphylococcus aureus and antifungal efficacy against the fungi Rhizopus stolonifer and Aspergillus niger.